Neuroscience, Wellbeing, and Urban Design: Our Universal Attraction to Vitality - Ellard, Colin (UI Scholars Hub, 2020)
Although urban planners and architects understand that there is a relationship between the design of urban settings and our thoughts and emotions, it is only recently that we have had the tools to properly dissect this relationship. New methods for measuring affective, physiological, and cognitive states in people immersed in virtual reality have generated a host of novel findings, but a consistent theme is the idea that human beings have a deep affinity for vitality at every level, from home interiors to urban streetscapes. Recent evidence also suggests that we respond to the vitality of scenes almost immediately, even after exposures as brief as 50 milliseconds, possibly using ambient visual processing mechanisms that rely on our peripheral visual field. Further, when we sense and respond to vitality, positive affect increases, which in turn promotes affiliation and protects us from urban loneliness. This paper presents findings from laboratory and field experiments that show the power of vitality to positively change behavior and improve psychological wellbeing. Harnessing this power in urban design is one of the keys to building a psychologically sustainable city.